COMMUNICATION COMPETENCE, JOB MOTIVATION AND TEACHING PERFORMANCE - Vanessa Joy Z. Judith (Izdevnieciba "Baltija Publishing", 2019)
This study determined the communication competence, job motivation and teaching performance of the faculty in Carlos Hilado Memorial State College for Academic Year 2015-2016 when taken as a whole and grouped according to sex, civil status, length of institutional service and academic rank and the significant difference and significant relation of communication competence and teaching performance. The descriptive method of research was used in this study. Stratified random sampling was employed in the selection participants. The Communication Competence Descriptive Questionnaire and the Job Motivation Questionnaire were utilized in this study both were validated and reliability tested. The data on teaching performance was provided by the Human Resource and Development Office and it was taken from the Faculty Evaluation Instrument. The Mean, standard deviation and One- Way were employed. The study revealed that: (1) the communication competence of the faculty of CHMSC was "high"; (2) as an entire group, the job motivation of the faculty varies; (3) the teaching performance of the faculty of CHMSC was "very satisfactory"; (4) there was no significant difference that exists between communication competence and civil status, sex, length of institutional service and academic rank; (5)there was no significant difference that exists between teaching performance and civil status, sex, length of institutional service and academic rank; (6)there was no significant relationship that exists between communication competence and teaching performance.